2007
DOI: 10.1038/sj.bjc.6603729
|View full text |Cite
|
Sign up to set email alerts
|

X-ray screening seems to reduce gastric cancer mortality by half in a community-controlled trial in Costa Rica

Abstract: X-ray screening of gastric cancer is broadly used in Japan, although no controlled trial has proved its effectiveness. This study evaluates the impact of an X-ray screening demonstrative intervention to reduce gastric cancer mortality in a Costa Rican region. The evaluation follows a quasi-experimental, community-controlled design, with measures before and after. About 7000 individuals participated by invitation in the two-wave screening programme. X-ray screening was followed by videoendoscopy and gastric bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 15 publications
0
10
0
2
Order By: Relevance
“…The perspectives for the control of gastric cancer are uncertain because therapeutic advances are insufficient, the pre-clinical results of efforts to develop vaccines against H. pylori have been disappointing 31 ; and the early detection of gastric cancer in Latin America has shown unreliable results 32 , 33 and low cost-effectiveness 34 . During the first stages of tumor growth, cancer is clinically silent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perspectives for the control of gastric cancer are uncertain because therapeutic advances are insufficient, the pre-clinical results of efforts to develop vaccines against H. pylori have been disappointing 31 ; and the early detection of gastric cancer in Latin America has shown unreliable results 32 , 33 and low cost-effectiveness 34 . During the first stages of tumor growth, cancer is clinically silent.…”
Section: Discussionmentioning
confidence: 99%
“…Las perspectivas para el control del cĂĄncer gĂĄstrico son inciertas porque son insuficientes los avances terapĂ©uticos, los resultados pre-clĂ­nicos de los esfuerzos para el desarrollo de vacunas contra H. pylori , han sido decepcionantes 31 ; y la detecciĂłn temprana del cĂĄncer gĂĄstrico en LatinoamĂ©rica ha mostrado resultados discordantes 32 , 33 y baja costo-efectividad 34 . Teniendo en cuenta que durante las primeras etapas del tumor es clĂ­nicamente silente, una alternativa para su control es la prevenciĂłn primaria mediante la erradicaciĂłn de la infecciĂłn por H. pylori que puede reducir el riesgo de desarrollar cĂĄncer gĂĄstrico en personas sin lesiones precursoras 30 , 34 , 35 .…”
Section: Discussionunclassified
“…Studies on gastric cancer screening considered reduction in gastric cancer mortality or intermediate outcomes (eg, gastric cancer detection rate) as outcomes. Observational studies suggested a statistically significant reduction of gastric cancer mortality for direct gastroscopy (odds ratio (OR) = 0.72, 95% CI 0.54 – 0.97) and X–ray (48–59%, P < 0.05) [ 30 , 34 ]. Screening with photofluorography was not found to reduce mortality from gastric cancer [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cohort studies have also shown mortality reduction by gastric radiographic screening . In Costa Rica also, gastric radiographic screening has been reported to be effective and is recognised as an effective method for reducing the mortality from gastric cancer. However, radiographic screening in that country has been reported to be associated with such problems as low participation rates, and a relatively low availability and aging of physicians with sufficient skills for interpreting gastric radiographs.…”
Section: Discussionmentioning
confidence: 99%